3–10 GHz self-biased resistive-feedback LNA with inductive source degeneration - Sui, W. Q. (2013)
A 3-10 GHz self-biased low-noise amplifier (LNA) implemented in Global Foundries 65 nm CMOS process is presented. A novel input-matching network employing the resistive feedback and inductive source degeneration techniques is proposed to achieve the wideband matching as well as low noise figure. The LNA exhibits a power gain of 17 - 1 dB over 3-10 GHz with noise figure ranging from 3.5 to 4.3 dB. The fabricated LNA occupies an area of 0.15 mm2 and draws 12 mA from 1.2 V power supply.